2017
DOI: 10.1007/s00784-017-2222-z
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic infections increase leukocyte and lymphocyte levels in the blood

Abstract: The presence of endodontic infections can interfere with the blood profile, altering systemic health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 42 publications
0
21
0
3
Order By: Relevance
“…Samuel et al . () demonstrated that the presence of apical periodontitis increased cytokine levels in blood. However, in both studies, researchers found this alteration was significant only in multiple apical periodontitis groups.…”
Section: Discussionmentioning
confidence: 99%
“…Samuel et al . () demonstrated that the presence of apical periodontitis increased cytokine levels in blood. However, in both studies, researchers found this alteration was significant only in multiple apical periodontitis groups.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental induction of AP in rats is a reliable and a generally accepted model for studying AP. The use of an experimental animal model allowed us to carry out the research under standardized conditions in which rats of the same strain, sex, and weight received the same food, experienced the same stress, and shared the same housing facilities .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study by Samuel et al . , it was demonstrated that the presence of AP stimulates elevation of cytokine levels in blood. However, in both studies, researchers found this alteration to be significant only in the presence of more than one tooth with AP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following parameters of the complete blood count were analysed using an automatic analyser (ABX Micros ABC Vet; Horiba ABX Diagnostics, Montpellier, France): haemoglobin, haematocrit, mean corpuscular volume (MCV), mean corpuscular haemoglobin concentration (MCHC), fibrinogen, total leucocytes, neutrophils, lymphocytes, eosinophils and monocytes (Samuel et al 2018). The samples were placed in EDTA, homogenized and immediately transferred to a technician, who was blinded to the case status, for processing.…”
Section: Blood Sample Collectionmentioning
confidence: 99%